Body Mass Index (BMI) in Children Aged 6-12 Years in Elementary School - Idris Idris; Andi Nursiah; Fatmawati Fatmawati; Isymiarni Syarif (Sarana Ilmu Indonesia (salnesia), 2023)
Body mass index is an objective measurement method that can be applied in measuring the relationship between a person's weight and height so that we can determine the risks to our body's health. This research aimed to identified the factors associated with the Body Mass Index (BMI) in children aged 6-12 years. The type of research used in this research was an analytic survey using a cross sectional study design. The number of samples used in this study were 59 subjects obtained by using a purposive sampling technique. the results in this study were obtained using the chi-square statistical test. The results showed breakfast habits p-value=0,000, physical activity p-value=0,005, snack habits at school p-value=0,000. From the value of the odds ratio, the value of breakfast=12,000, snack habits=61,200 and physical activity=8,000 can also be concluded that there is a relationship between breakfast habits, physical activity and snack habits with body mass index in elementary school students from the odds ratio value it is said that Snacking habits are the variable that has the greatest risk of causing BMI problems by 61 times. So, it is necessary to routinely measure the height and weight of students so that the nutritional status of students can be known.